Salinity endurance of marine macro Rhodophycean algae with special emphasis on myo-inositol biosynthesis: An enzymological analysis from Halymenia venusta Børgesen - Mahanty, Dibyendu Sekhar; Basu, Sautrik; Adhikari, Jukta (Journal of Plant Stress Physiology, 2021)
Altered salinity is one the most important perils encountered by marine plants inclusive of algae. Under hyper saline condition plants accumulate several stress relieving osmolytes including myo-inositol, the most widespread cyclitol in plants. The present communication reports the occurrence of myo-inositol biosynthesis in six different Rhodophycean seaweeds growing under stressful intertidal habitats of the Okha coast (Gujarat, India), on the basis of a study conducted on two marker enzymes of myo-inositol biosysnthesis [L-myo-inositol-1-phosphate synthase and D/L-myo-inositol-1-phosphate phosphatise]. Both enzymes were partially purified from Halymenia venusta to about 27 and 39 folds respectively over the homogenate following low-speed centrifugation, 30-75% ammonium sulphate fractionation, successive chromatography through DEAE-cellulose / CM-Cellulose, Sephadex G-200 and BioGel 0.5m / UltrogelAcA 34 columns. The temperature and pH optima for both the enzymes were similar and were recorded to be 350C and 7.5 respectively. For MIPS, D-glucose-6-phosphate and NAD were the exclusive substrate and coenzyme respectively and D/L-MIP was the sole substrate for MIPP. The Km values for D-glucsoe-6-phosphate and β-NAD were recorded to be 3.599 mM and 0.2366 mM respectively, while the Km value for D-MIP was found to be 0.4070 mM. Monovalent cations K+ had slight stimulatory, Li+ was strong inhibitory for both the enzymes. Divalent cations Ca2+ exhibited slight stimulatory and Cd2+ reduced MIPS and MIPP activities. MIPP was stimulated by Mg2+. Cu2+ and Hg2+ were strong inhibitors of both the enzymes. A steady and proportionate increase in the content of free myo-inositol was observed along with elevated levels of recorded salinity.